2010
DOI: 10.1007/s13209-010-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

The causes and economic consequences of envy

Abstract: In this lecture I first give an explanation for invidious preferences based on the (evolutionary) competition for resources. Then I show that these preferences have wide ranging and empirically relevant effects on labor markets, such as: workplace skill segregation, gradual promotions, wage increases that have no relation with productivity and downward wage flexibility. I suggest that labor and human resource economics can benefit from including envy into the standard set of factors considered in their theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…For future multilevel research, I would encourage researchers to consider situational and episodic envy as a potential emotional response to pay dispersion. Cabrales (2010) highlights the importance of envy in a theoretical economic model and demonstrates that damaging invidious reactions are quite likely in situations in which "increases have no relation with productivity" (p. 371), which bear a striking resemblance to the unexplained pay dispersion situations examined by several authors noted in this review. What is provocative about envy in the realm of pay dispersions is that the behavioral consequences of envy are negative only in a limited set of circumstances (Duffy et al 2012).…”
Section: Expanded Criteriamentioning
confidence: 54%
“…For future multilevel research, I would encourage researchers to consider situational and episodic envy as a potential emotional response to pay dispersion. Cabrales (2010) highlights the importance of envy in a theoretical economic model and demonstrates that damaging invidious reactions are quite likely in situations in which "increases have no relation with productivity" (p. 371), which bear a striking resemblance to the unexplained pay dispersion situations examined by several authors noted in this review. What is provocative about envy in the realm of pay dispersions is that the behavioral consequences of envy are negative only in a limited set of circumstances (Duffy et al 2012).…”
Section: Expanded Criteriamentioning
confidence: 54%
“…As for the Pessimist phenotype, we have not been able to draw a clear relationship to the types most commonly found among social value orientations, but in any event the similarities between the two classifications is appealing and suggests an interesting line for further research. Another alternative view on our findings arises from social preferences theory (23), where, for instance, envy can be understood as the case in which inequality that is advantageous to self yields a positive contribution to one's utility (39)(40)(41)(42). Altruists can be viewed as subjects with concerns for social welfare (39), whereas for the other phenotypes, we find it difficult to understand them in this framework and, in fact, optimists and pessimists do not seem to care about their partner's outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many scholars argue that envy in its purest form creates a "call to action" to solve the source of any inferiority felt (Plutchik, 2002;Smith and Kim, 2007). Economically, some consider consumer envy a more optimistic form of envy which can spark overall productive economic activity (Belk, 2008;Cabrales, 2010). Recently, empirical evidence demonstrated that envy can produce positive economic reactions such as an inclination to purchase an envy-elicited product (Van de Ven et al, 2011).…”
Section: Interpersonal and Organizational Consequences Of Consumer Envy During Service Encountersmentioning
confidence: 99%